Infection Control in Dentistry in the Ebola Era - Hoyle, Brian (MD Conference Express, 2014)
At the time of the session, the ongoing Ebola outbreak in West Africa had killed nearly 4500 people, including more than 200 health care workers, likely an underestimate of the actual numbers. In a worst-case scenario, the World Health Organization and US Centers for Disease Control and Prevention estimate that the number of cases could reach almost 1.5 million by early 2015. This article discusses infection control in dentistry. At the time of the session, the ongoing Ebola outbreak in West Africa had killed nearly 4500 people, including more than 200 health care workers, likely an underestimate of the actual numbers. In a worst-case scenario, the World Health Organization and US Centers for Disease Control and Prevention estimate that the number of cases could reach almost 1.5 million by early 2015. This article discusses infection control in dentistry. At the time of the session, the ongoing Ebola outbreak in West Africa had killed nearly 4500 people, including more than 200 health care workers, likely an underestimate of the actual numbers. In a worst-case scenario, the World Health Organization and US Centers for Disease Control and Prevention estimate that the number of cases could reach almost 1.5 million by early 2015. This article discusses infection control in dentistry. At the time of the session, the ongoing Ebola outbreak in West Africa had killed nearly 4500 people, including more than 200 health care workers, likely an underestimate of the actual numbers. In a worst-case scenario, the World Health Organization and US Centers for Disease Control and Prevention estimate that the number of cases could reach almost 1.5 million by early 2015. This article discusses infection control in dentistry. At the time of the session, the ongoing Ebola outbreak in West Africa had killed nearly 4500 people, including more than 200 health care workers, likely an underestimate of the actual numbers. In a worst-case scenario, the World Health Organization and US Centers for Disease Control and Prevention estimate that the number of cases could reach almost 1.5 million by early 2015. This article discusses infection control in dentistry. At the time of the session, the ongoing Ebola outbreak in West Africa had killed nearly 4500 people, including more than 200 health care workers, likely an underestimate of the actual numbers. In a worst-case scenario, the World Health Organization and US Centers for Disease Control and Prevention estimate that the number of cases could reach almost 1.5 million by early 2015. This article discusses infection control in dentistry.